CUIDADOS DE ENFERMAGEM ONCOLÓGICA HUMANIZADOS - Marques, Paulo Alexandre Oliveira; Lopes, Ana Sofia Magalhães; Ribeiro, Ana Lúcia Barbosa; Santos, Daniela Francisca de Oliveira (Cogitare Enfermagem, 2024)
Editorial.